A Numerical Evaluation for a Newly Designed Closed Loop Subsonic Wind Tunnel - Ali, Ridha Mohammed; Alsahlani, Ahmad A. (Basrah Journal for Engineering Sciences, 2024)
A wind tunnel is a piece of equipment specifically designed for studying the influence of air passing over solid matters in aerodynamic research. Computational Fluid Dynamics (CFD) was used to conduct methodical research into the design and modeling of flow characteristic in a closed-loop wind tunnel. The necessary intake fan velocity was established using an analytical velocity model, and the test section's inlet conditions were produced by applying the Reynolds number equation, assuming that the Reynolds number was 500,000. Instead than using the traditional method, a full-scale CFD model of the complete wind tunnel was taken into consideration. This made it possible to improve the flow quality over the entire circuit as well as only in the test area. The test section flow quality was more impacted by upstream flow circumstances than downstream conditions, according to analysis of the guide vane designs. Therefore, careful consideration has to be done while constructing the vanes at upstream curves, especially corners that are parallel to the test section. The simulation results showed that, in the case of a fully configured wind tunnel, flow uniformity in the test section is successfully attained.